2008
DOI: 10.1149/1.2901864
|View full text |Cite
|
Sign up to set email alerts
|

Composite Polymer Core–Silica Shell Abrasives: The Effect of the Shape of the Silica Particles on Oxide CMP

Abstract: We use oxide chemical mechanical planarization ͑CMP͒ as a convenient test vehicle for comparing the material removal rate and defectivity induced by different silica abrasives. The effect of particle shape is investigated by comparing fumed and colloidal silica. In particular, the effect of a polymer core on the behavior of a composite abrasive is explored. Overall, fewer and shallower scratches are detected for the composites with a colloidal silica shell as compared with colloidal silica, as well as composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Also, the larger size of colloidal silica shows a higher number of defects level than the smaller size of colloidal silica. The interaction force and composite particle morphology were also described in other works [53,54]. Based on the average pull-off force vs. pH plot, qualitative agreement between the measured adhesion forces and the material removal rate was reached [53].…”
Section: High Particle Concentration and Agglomerated Particlesmentioning
confidence: 66%
See 1 more Smart Citation
“…Also, the larger size of colloidal silica shows a higher number of defects level than the smaller size of colloidal silica. The interaction force and composite particle morphology were also described in other works [53,54]. Based on the average pull-off force vs. pH plot, qualitative agreement between the measured adhesion forces and the material removal rate was reached [53].…”
Section: High Particle Concentration and Agglomerated Particlesmentioning
confidence: 66%
“…Furthermore, the depth of the scratch increased with increasing abrasive size of fumed silica abrasive. Overall, fewer and shallower scratches were detected for composite B particle with a colloidal silica shell compared with only colloidal silica due to the effect of the elasticity of the polymer core [54].…”
Section: High Particle Concentration and Agglomerated Particlesmentioning
confidence: 96%
“…Organic/inorganic composite particles with a core-shell structure exhibit potential applications in chemical mechanical polishing/planarization (CMP) for mechanically challenging materials (copper and low-k dielectrics etc.). Armini and coworkers 8,9 improved the CMP behaviors for copper and SiO 2 dielectric layer using the composite polymer-silica core-shell submicrometer particles. Particularly, the types of surface defects aer polishing were classied and quantied by using a confocal review station.…”
Section: Introductionmentioning
confidence: 99%
“…To reduce the defectivity after polishing, Armini and coworkers [12,13] investigated the effects of particle (fumed and colloidal silica) shape and size on oxide CMP performances. The experimental results indicated that fewer and shallower scratches were detected for the composites with a colloidal silica shell as compared with colloidal silica, as well as the composites with a fumed silica shell.…”
Section: Introductionmentioning
confidence: 99%